Державне регулювання використання повітряного простору України - Брусакова, О. В.; Brusakova, O. V. (Науковий вісник публічного та приватного права. - 2019. - Вип. 6. - С. 142-148, 2019)
Досліджено поняття та зміст державного регулювання використання повітряного простору України. Наголошено, що державне регулювання використання повітряного простору є діяльністю уповноважених суб’єктів, що здійснюється ними з приводу польотів повітряних суден, переміщення (перебування) матеріальних об’єктів у повітряному просторі України, здійснення ряду інших робіт і діяльності, пов’язаної з використанням повітряного простору, шляхом реалізації комплексу законодавчо закріплених засобів задля гарантування безпеки авіації, забезпечення інтересів держави, національної безпеки та потреб суспільства й економіки в повітряних перевезеннях та авіаційних роботах.

In the article it has been emphasized the importance of defining the concept and content of the state regulation of the use of Ukrainian airspace. The author has defined the concept of “state regulation of the use of Ukrainian airspace”. The author has defined the state regulation of the use of airspace as the activity of authorized entities, which they perform in connection with flights of aircraft, the movement (stay) of material objects in the airspace of Ukraine, the implementation of a number of other works and activities related to the use of airspace , through the implementation of a set of statutory means to guarantee the safety of aviation, ensure the interests of the state, national security and the needs of society and economy in the air and air traffic operations. The main measures by which state regulation of the use of airspace is carried out are the granting of permits, conditions, prohibitions and restrictions on the use of airspace; establishment of airspace structure; consolidation of air traffic service routes; implementation of airspace classification; planning and coordinating the use of airspace; consideration of applications for the use of airspace; coordination of airspace-related activities and civilian-military coordination; determining the procedure for crossing the state border aircraft and using the airspace of an area with a special regime of airspace use; exercising control over the observance of the rules and rules for the use of Ukrainian airspace. It has been analyzed the normative-legal acts, at the level of which the legal bases of realization of state regulation of the use of Ukrainian airspace are fixed, taking into account their legal force. The normative basis for the implementation of these measures of state regulation of the use of airspace is a considerable number of legal acts: the Constitution of Ukraine, international treaties of Ukraine, acts of codified legislation and laws of Ukraine, by-laws and regulations. Among the latter are the normative acts, which were adopted jointly by the State Aviation Service and the Ministry of Defense of Ukraine.

Исследованы понятие и содержание государственного регулирования использования воздушного пространства Украины. Отмечено, что государственное регулирование использования воздушного пространства является деятельностью уполномоченных субъектов, осуществляемой ими в связи с полётам воздушных судов, перемещения (нахождения) материальных объектов в воздушном пространстве Украины, осуществления ряда других работ и деятельности, связанной с использованием воздушного пространства путем реализации комплекса законодательно закрепленных средств для обеспечения безопасности авиации, обеспечения интересов государства, национальной безопасности и потребностей общества и экономики в воздушных перевозках и авиационных работах.
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; авіаційна галузь; aviation industry; авиационная отрасль; державне регулювання; state regulation; государственное регулирование; використання повітряного простору; use of air space; использование воздушного пространства; правове регулювання; legal regulation; правовое регулирование; повітряний простір; airspace; воздушное пространство; правові засади; legal principles